A bird’s eye view on the Islamic discourse in Indonesia - Ahmad H.Osman, Rahmah; Nasir, Mohd Shahrizal (Center for Promoting Ideas (CPI), 2011)
This study takes a quick look at the Islamic literature discourse in Indonesia. This study seems essential considering the fact that the names of many Indonesian writers, especially Hamka, have been mentioned on several occasions in the discussions on Islamic literature in Malaysia. The arguments presented in this study have been carefully chosen from previous studies, carried out by E.U. Kratz (1986, 1997), Ungku Maimunah Mohd. Tahir (1990), Peter Riddell (2001) and articles published in the Indonesian journals, Horison and Panji Masyarakat. A point to be noted from the beginning however, is that we do not propose a detailed study of the Islamic literature discourse in Indonesia but merely to look at it as a whole. This is because the Indonesian Islamic literature discourse deserves an extensive study of its own. However, for the purpose of general comparison, some points in the Indonesian discourse, which stand out even at a cursory glance, are taken up for discussion.